Fear Mongering 2.0: Dialogic Disruption and Interpersonal Trust Crisis in Post-Protest Social Media Discourse Following the August 23, 2025 Demonstrations in Indonesia - Julia Magdalena Wuysang,; Ira Patriani,; Rahmawati,; Feibe Engeline Pijoh, (Technium Social Sciences Journal, 2026)
The phenomenon of "Fear Mongering 2.0" reveals a critical rupture in dialogic reciprocity and a deepening interpersonal trust crisis within post-protest social media discourse following the mass demonstrations on September 23, 2025, in Indonesia. Triggered by widespread public outrage over parliamentary tax privileges and allowances, social media platforms transformed into contested spaces not merely for political expression but for the algorithmic proliferation of fear-driven narratives. These emotionally charged discourses, amplified by platform logics, generated moral panic, intensified group polarization, and eroded the affective conditions necessary for meaningful interpersonal communication. Employing a critical qualitative research approach, this study uncovers three key findings: (1) social media algorithms function not as neutral infrastructures but as affective agents of power that reshape interpersonal communication into an arena governed by emotional visibility rather than deliberative meaning-making (cf. Zuboff, 2019; Papacharissi, 2015); (2) algorithmically induced fear mongering disrupts the continuity of interpersonal relationships through the production of emotional dissonance and affective misalignment among individuals previously bonded by emotional proximity and mutual trust (cf. Ahmed, 2014; Gillespie & Dietz, 2009); and (3) dialogic breakdown in the post-protest context cannot be reduced to spontaneous social tensions but must be understood as the outcome of structured interventions via algorithmic silencing and emotional engineering deployed by digital platforms (cf. Noble, 2018; DeVito, 2017). This study thus positions post-protest social media as a site of symbolic struggle that undermines the ethics of interpersonal dialogue in the digital age.